2017
DOI: 10.1200/jco.2017.35.15_suppl.tps9596
|View full text |Cite
|
Sign up to set email alerts
|

CARSKIN: Pembrolizumab as first line therapy in patients with unresectable cutaneous squamous cell carcinoma (cSCC).

Abstract: TPS9596 Background: Treatment options are limited for patients (pts) with locally advanced or metastatic cSCCs. Cisplatin-based combinations have some efficacy but their toxicity often prohibits their use, particularly for the elderly. New therapeutic options are needed. Tumors divert the programmed death receptor 1 (PD-1) pathway suppressing immune control. Pembrolizumab (MK-3475) is a high-affinity humanized monoclonal anti-PD-1 antibody. It leads to dual PD-1 ligand (PD-L1 and PD-L2) blockade that may reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…This case report highlights the occasional dramatic effect of PD-1 inhibition for the treatment of cSCC and it remains to be determined if this medication could outperforms cemiplimab in regard to efficacy or safety. Unpublished reports from a small (N=39) phase II clinical trial (CARSKIN, NCT02883556) study evaluating pembrolizumab as first-line monotherapy for unresectable cSCCs demonstrated robust antitumor activity regardless of PD-L1 expression levels and suggests similarly high efficacy compared to cemiplimab [16]. The lack of randomized, head-to-head comparisons of cemiplimab and pembrolizumab limit the ability to comment on the individualized risk:benefit anaylsis and approach to locally advanced or metastatic cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…This case report highlights the occasional dramatic effect of PD-1 inhibition for the treatment of cSCC and it remains to be determined if this medication could outperforms cemiplimab in regard to efficacy or safety. Unpublished reports from a small (N=39) phase II clinical trial (CARSKIN, NCT02883556) study evaluating pembrolizumab as first-line monotherapy for unresectable cSCCs demonstrated robust antitumor activity regardless of PD-L1 expression levels and suggests similarly high efficacy compared to cemiplimab [16]. The lack of randomized, head-to-head comparisons of cemiplimab and pembrolizumab limit the ability to comment on the individualized risk:benefit anaylsis and approach to locally advanced or metastatic cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended doses are 3 mg for kilograms of weight every 3 weeks as intravenous (iv) infusion for a period of 30 minutes. Among the different PD-1 inhibitors, the number of patients treated is the widest, about 28 reported in the literature (Assam et al, 2016;Borradori et al, 2016;Chang et al, 2016;Degache et al, 2018;Deinlein et al, 2017;Ferrarotto, 2017;Lipson et al, 2016;Ravulapati et al, 2017;Stevenson et al, 2017;Tran et al, 2017;Winkler et al, 2017;Zalaudek et al, 2019), excluding the ongoing trials in Phase I and II (Licitra et al, 2017;Kudchadkar et al, 2018;Maubec et al, 2019). Although the larger number of reported cases, responses data are not enough and in addition with short period of follow-up.…”
Section: Pembrolizumabmentioning
confidence: 99%
“…Nowadays, the widest open trial is KEYNOTE‐629, a Phase II study enrolling 120 patients with Stage III and IV disease (Licitra et al, ) (LE 1b following Oxford CEBM Levels of Evidence). Maubec et al () reported partial results of the Stage I trial (CASKIN), including 19 patients (LE 1b following Oxford CEBM Levels of Evidence). Response rate (RR) of 42% at 15 weeks, corresponding to seven partial response (PR) and one complete response (CR) and only one responder progressed.…”
Section: Introductionmentioning
confidence: 99%
“…At the 2019 ASCO meeting, a French trial using pembrolizumab in the same schedule (NCT02883556) in unresectable cSCC with no prior systemic therapy was also reported 3 . Of 39 patients by 15 weeks, there were 2 complete and 13 partial responses for an ORR of 38.5%.…”
Section: Other Immune Checkpoint Inhibitormentioning
confidence: 99%